2018
DOI: 10.1101/322693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of differentially methylated regions in primates and non-primates provides support for the evolutionary hypothesis of schizophrenia

Abstract: IntroductionThe persistence of schizophrenia in human populations separated by geography and time led to the evolutionary hypothesis that proposes schizophrenia as a by-product of the higher cognitive abilities of modern humans. To explore this hypothesis, we used here an evolutionary epigenetics approach building on differentially methylated regions (DMRs) of the genome.MethodsWe implemented a polygenic enrichment testing pipeline using the summary statistics of genome-wide association studies (GWAS) of schiz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Building up on their study, we found that the human specific differentially methylated regions (hDMRs) show an enrichment of genetic variants associated with schizophrenia (compared to the rest of the genome [24]). While regions differentially methylated between human and great apes [25] do not show such an enrichment.…”
Section: Introductionmentioning
confidence: 86%
“…Building up on their study, we found that the human specific differentially methylated regions (hDMRs) show an enrichment of genetic variants associated with schizophrenia (compared to the rest of the genome [24]). While regions differentially methylated between human and great apes [25] do not show such an enrichment.…”
Section: Introductionmentioning
confidence: 86%